1989
DOI: 10.1111/j.1349-7006.1989.tb01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphokine‐activated Killer Induction and Its Regulation by Macrophages in Malignant Pleural Effusions

Abstract: Mononuclear cells (MNC) from pleural effusions and peripheral blood of 18 patients with primary lung cancer with malignant pleural effusion were studied. Pleural and blood MNC generated lymphokine‐activated killer (LAK) activity similarly when cultured for 4 days with an optimal concentration of interleukin 2 (IL‐2). Highly purified lymphocytes (>98%) and monocyte‐macrophages (>90%) were isolated by discontinuous Percoll gradient centrifugation from pleural and blood MNC. Pleural macrophages, as well as blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Our previous investigations showed that approximately 80% of lymphocytes in malignant pleura! effusions before therapy consisted of CD3' cells, and that intrapleural injections of lL-2 resulted in increase in number of T lymphocytes [26]. suggesting that IL-2-aetivated T lymphocytes may contribute to the augmented levels of IL-6 after IL-2 infusions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous investigations showed that approximately 80% of lymphocytes in malignant pleura! effusions before therapy consisted of CD3' cells, and that intrapleural injections of lL-2 resulted in increase in number of T lymphocytes [26]. suggesting that IL-2-aetivated T lymphocytes may contribute to the augmented levels of IL-6 after IL-2 infusions.…”
Section: Discussionmentioning
confidence: 99%
“…The recent finding that tumour cells themselves produce IL-6 also indicates the possibility that a responseofthelungcancereells to IL-2 may have contributed to the observed increase of IL-6. All our patients with a clinical response to IL-2 showed that the lung cancer cells in the efTusions disappeared within 5 days [26]. Thus, it is unlikely that (/; livn induction of lL-6 on IL-2 infusion was produced by the lung cancer cells in the effusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…respectively. as described previously (Sone et al 1987: Yanagawa et al 1989). The resultant MNCs (105 per well) were incubated in CRPMI-1640.…”
Section: Methodsmentioning
confidence: 99%